Makna Perjamuan Kudus dalam Membangun Tubuh Kristus berdasarkan 1 Korintus 10-11 dan Implementasinya bagi Remaja - Priadi Roby; Jefit Sumampouw; Doni Heryanto (Sekolah Tinggi Alkitab Jember, 2026)
The Lord’s Supper is a central sacrament in Christian worship that embodies both theological and ecclesiological significance in shaping the church as the Body of Christ. However, in contemporary church practice, particularly in youth ministry, it is often understood primarily as a ritual observance rather than a formative means of communal spirituality. This article aims to (1) examine the meaning of the Lord’s Supper through an exegetical-theological study of 1 Corinthians 10–11, (2) explain its role in building the Body of Christ within Pauline ecclesiology, and (3) explore its implications for Christian youth faith formation. Employing a qualitative descriptive method with an exegetical approach, this study analyzes biblical texts alongside relevant literature in New Testament theology, sacramental theology, and Christian education. The findings reveal that the Lord’s Supper signifies koinonia with Christ and with fellow believers, fostering unity, equality, love, and social responsibility within the church. The novelty of this study lies in integrating Pauline sacramental theology with a contextual framework for youth spiritual formation. Perjamuan Kudus merupakan salah satu sakramen utama dalam ibadah Kristen yang memiliki makna teologis dan eklesiologis dalam membentuk gereja sebagai Tubuh Kristus. Namun, dalam praktik gereja masa kini, khususnya dalam pelayanan remaja, Perjamuan Kudus sering dipahami terutama sebagai ritual liturgis daripada sebagai sarana pembentukan spiritualitas komunal. Artikel ini bertujuan untuk (1) mengkaji makna Perjamuan Kudus melalui studi eksegetis-teologis terhadap 1 Korintus 10–11, (2) menjelaskan perannya dalam membangun Tubuh Kristus dalam kerangka eklesiologi Paulus, dan (3) menguraikan implikasinya bagi pembinaan iman remaja Kristen. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan eksegetis terhadap teks Alkitab, yang didukung oleh kajian literatur dalam teologi Perjanjian Baru, teologi sakramen, dan pendidikan Kristen. Hasil penelitian menunjukkan bahwa Perjamuan Kudus merupakan perwujudan koinonia dengan Kristus dan sesama orang percaya yang membangun kesatuan, kesetaraan, kasih, serta tanggung jawab sosial dalam gereja. Kebaruan penelitian ini terletak pada integrasi teologi sakramental Paulus dengan pendekatan kontekstual bagi pembinaan spiritual remaja Kristen.